2018
DOI: 10.1007/s00134-018-5245-2
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-hours discharge from intensive care, in-hospital mortality and intensive care readmission rates: a systematic review and meta-analysis

Abstract: PurposeDischarge from an intensive care unit (ICU) out of hours is common. We undertook a systematic review and meta-analysis to explore the association between time of discharge and mortality/ICU readmission.MethodsWe searched Medline, Embase, Web of Knowledge, CINAHL, the Cochrane Library and OpenGrey to June 2017. We included studies reporting in-hospital mortality and/or ICU readmission rates by ICU discharge “out-of-hours” and “in-hours”. Inclusion was limited to patients aged ≥ 16 years discharged alive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 42 publications
(136 reference statements)
1
70
0
3
Order By: Relevance
“…Yapılan çalışmalarda YBÜ'ye başvuru sırasındaki hastalığın ciddiyeti yüksek olmasının ve gece veya mesai dışı taburculuğun YBÜ'ye yeniden başvuruda bağımsız bir risk faktörü olduğunu göstermiştir (9,10). Çalışmamızda aynı ekip tarafından yalnızca mesai içinde yapılan taburculukları değerlendirerek yeniden başvuru için ayrıca risk olan bu Yoğun bakımda yatışları sırasında mekanik ventilasyon desteği alan hastaların almayanlara göre taburculukları sonrasında daha sık yoğun bakıma yeniden başvurduğunu belirledik.…”
Section: Discussionunclassified
“…Yapılan çalışmalarda YBÜ'ye başvuru sırasındaki hastalığın ciddiyeti yüksek olmasının ve gece veya mesai dışı taburculuğun YBÜ'ye yeniden başvuruda bağımsız bir risk faktörü olduğunu göstermiştir (9,10). Çalışmamızda aynı ekip tarafından yalnızca mesai içinde yapılan taburculukları değerlendirerek yeniden başvuru için ayrıca risk olan bu Yoğun bakımda yatışları sırasında mekanik ventilasyon desteği alan hastaların almayanlara göre taburculukları sonrasında daha sık yoğun bakıma yeniden başvurduğunu belirledik.…”
Section: Discussionunclassified
“…We note that it is more conventional to use readmission (or mortality) within 48 hours to define a negative outcome related to ICU care [12,26]. However, this practice is not universal [27] and in our case it was not possible because of limitations in the data available locally. Given the low rates of negative outcome following callout in both MIMIC and GICU (see table 2), we generated further instances of the negative class, in order to balance the class sizes.…”
Section: Readiness-for-dischargementioning
confidence: 93%
“…The observational study by Connors et al [5], questioning the use of pulmonary artery catheterization in the management of critically ill patients, is a classic example of a study that revealed unexpected results using existing data, and consequently led to critical reappraisal of a common practice (even though suggested harm was not confirmed by experimental studies) [6]. Observational studies using administrative data can also offer insights in situations where an intervention simply cannot be randomly allocated in any practical way, e.g., in studying the (potentially harmful) effects of premature discharge at night [7].…”
Section: Randomization Is Not the Only Road To Causal Inferencementioning
confidence: 99%